People get ready : the future of jazz is now! - Heble, Ajay, 1961-; Wallace, Rob, 1976- (Improvisation, community, and social practice., 2013)
Jazz musicians, scholars, and journalists emphasize how the political consciousness that infused jazz in the 1960s and 1970s has continued to animate the avant-garde, Free Jazz, fusion, and other forms of this lively, always-evolving music.